Effect of Colchicine on Morphological Characteristics of Cayenne Pepper (Capsicum frutescence L.) - Makhziah Makhziah; Kezia Putri; Pangesti Nugrahani (Nusantara Science and Technology Proceedings, 2023)
Increasing the yield and quality of cayenne pepper can be obtained by expanding the size of the cayenne pepper fruit, while the size of the cayenne pepper fruit can be expanded through polyploidy mutation. The research aims to increase the size of the small fruit and plants of cayenne pepper. A single factor experiment was designed in a randomized block design which was repeated five times. The soaking colchicine solution treatment for cayenne pepper seeds consists of 0 ppm; 1 ppm; 5 ppm; and 1 ppm plus dripping colchicine on the shoot buds after the second leaf appeared; 5 ppm colchicine with dripping colchicine on the shoot buds after the second leaf appeared. The data recorded included morphological characters at the seedling and plant phases and then analyzed variance and honest significant difference tests using the Excel-Program. Results showed that the application of colchicine 1 and 5 ppm plus dripping colchicine on the shoot buds after the second leaf appeared were significantly different with no dripping colchicine on shoot buds in seedling height, seedling leaves number, and seedling leaves area. At the plant phase, the highest leaves area was obtained by application of colchicine 1 and 5 ppm without dripping at shoot buds and control (0 ppm) treatments, however highest diameter of fruits achieved by colchicine 1 and 5 ppm with dripping it at shoot buds and highest fruit number observed at no colchicine (control) treatment.